2017
DOI: 10.4236/ojce.2017.71004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Constituent Materials Properties on the Compressive Strength of in Situ Concrete in Kenya

Abstract: The poor quality of Kenyan in situ concrete has necessitated research to establish the properties of the ingredient materials and their influence on the troubling rate of failure of reinforced concrete structures in the country during construction and usage. The compressive strength of concrete relies on the properties of the constituent materials, proportions of the mixture, workmanship, compaction method and curing conditions. This paper outlines findings of an experimental investigation on the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, the closely related concrete compressive strengths (13.5 MPa, 10.5 MPa and 14.5 MPa) observed in building sites 8, and 4 and 15 respectively, despite the different concrete mix ratios adopted, could be attributed to variations in the quality of the component materials used for the concrete productions. Okumu et al (2017) in their research observed that, poor quality materials (sand, gravel, etc.) largely affected the compressive strength of the in-situ concrete produced.…”
Section: Compressive Strengthmentioning
confidence: 98%
“…Furthermore, the closely related concrete compressive strengths (13.5 MPa, 10.5 MPa and 14.5 MPa) observed in building sites 8, and 4 and 15 respectively, despite the different concrete mix ratios adopted, could be attributed to variations in the quality of the component materials used for the concrete productions. Okumu et al (2017) in their research observed that, poor quality materials (sand, gravel, etc.) largely affected the compressive strength of the in-situ concrete produced.…”
Section: Compressive Strengthmentioning
confidence: 98%
“…Concrete has been used globally over several decades for the construction of civil engineering projects and continue to be the ultimate building material for infrastructural development [1]. Since its application in civil and structural works, it has demonstrated durability and strength over time lasting for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are differences regarding the types of additives and the quantities used in the blended cement types used in various countries and within the same country. Quality assurance of construction materials plays a significant role on structural integrity, serviceability, and durability of constructed infrastructures [4]. The properties of construction materials and compliance with design specification become the major factor responsible for premature failure of buildings in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that none of the brands of the blended Portland cement achieved the target design strength for >C25 concrete. Okumu et al (2016) reports that none of the Kenya blended cement achieve the target design strength at 28 days of age and it continues to gain significant amount of compressive strength even beyond 90 days [12]. Yan Feng et al ( 2019) also reported a reduction on the compressive strength and strength development rate on blended cement mortar due to the effect of ultrafine granulated copper slag [6].…”
Section: Introductionmentioning
confidence: 99%